Réponses

2013-04-29T18:47:54+02:00

2.7 )

 

A = 2(x – 1) + 2(y + 2) – 2(1 + z) 

A=  2x -2 +2y +4 -2 -2z

  = 2x +2y -2z

 

 B = 3x – (3 – 3y) + 3(z + 1) 

 B = 3x -3 +3y +3z +3

     =  3x + 3y +3z 

 

C= (x+y-1) + (x+y +1) - (x+y-z)

C= x+y -1 +x +y +1 -x -y +z

C= x +y +z

 

D= 2(x – y) + 3(y – z) + 4(z – x) + 3x 

D= 2x -2y +3y -3z +4z -4x+ 3x 

D= -2x +y +z 

 

E = x(1 – y) + y(1 – z) + z(1 – x) + xy + yz + xz

E = x -xy +y - yz +z - xz +xy +yz +xz

    = x+y +z.

 

F= x – [(1 – y) – (z + 1)]

F= x-  ( 1-y -z -1)

  = x-1 +y +z +1

  = x +y +z.